2003
DOI: 10.1136/bmj.327.7419.837
|View full text |Cite
|
Sign up to set email alerts
|

Managing multiple morbidity in mid-life: a qualitative study of attitudes to drug use

Abstract: Objective To examine attitudes towards drug use among middle aged respondents with high levels of chronic morbidity. Design Qualitative study with detailed interviews. Setting West of Scotland. Participants 23 men and women aged about 50 years with four or more chronic illnesses. Main outcome measure Participants' feelings about long term use of drugs to manage chronic multiple morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
165
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(175 citation statements)
references
References 12 publications
9
165
0
1
Order By: Relevance
“…10,20,21 We separately examined older adults' preferences for participating in health care decisions with doctors and family and close friends using the following categories: Bmaking decisions independently, with or without advice^, Bshare decisions^and Bleave decisions up to them.^Finally, we developed questions to assess older adults' perspectives on their experiences managing their health, drawing on prior work to articulate disease-specific treatment burden. 6,7,[22][23][24] We constructed a summary measure that identified participants who reported that one or more of four individual experiences relating to treatment burden occur Bsometimes^or Boften.Ĉ ovariates We examine older adults' age, gender, educational attainment, self-rated health, numbers of chronic medical conditions, selfreported hospitalization in the prior year, and sensory impairment. Depressive symptoms were measured using established cut-points of the PHQ-2.…”
Section: Study Outcomesmentioning
confidence: 99%
“…10,20,21 We separately examined older adults' preferences for participating in health care decisions with doctors and family and close friends using the following categories: Bmaking decisions independently, with or without advice^, Bshare decisions^and Bleave decisions up to them.^Finally, we developed questions to assess older adults' perspectives on their experiences managing their health, drawing on prior work to articulate disease-specific treatment burden. 6,7,[22][23][24] We constructed a summary measure that identified participants who reported that one or more of four individual experiences relating to treatment burden occur Bsometimes^or Boften.Ĉ ovariates We examine older adults' age, gender, educational attainment, self-rated health, numbers of chronic medical conditions, selfreported hospitalization in the prior year, and sensory impairment. Depressive symptoms were measured using established cut-points of the PHQ-2.…”
Section: Study Outcomesmentioning
confidence: 99%
“…The efficacy of anti-depressants for mild depression has been questioned (Moncrieff & Kirsch, 2005) and they are not recommended to be used routinely by people with persistent sub-threshold depressive symptoms or mild depression in the first instance (NICE, 2010). There is also a range of side effects (Demyttenaere, 2003), many people do not like taking medicines (Maxwell, 2005;Givens et al, 2006;Townsend, Hunt, & Wyke, 2003;Kessing, Vibe Hansen, Demyttenaere, & Bech, 2005) and early drop-out rates in clinical trials vary from 12% to 40% (Cipriani et al, 2009;Kirsch et al, 2008). Psychological therapies are resource intensive, and may require cognitive capabilities a person with depression cannot attain.…”
Section: Introductionmentioning
confidence: 99%
“…9 Qualitative work has established that the main issues affecting patients with multimorbidity include loss of function, multiple medicine use, and negative effects on wellbeing, relationships, and coordination of care. 10,11 In addition, patients with multimorbidity often know a lot about managing their conditions and are actively engaged in self-management. However, they also have an interest in, and require support from, an enabling multidisciplinary health professional team.…”
Section: Introductionmentioning
confidence: 99%